Moving Backgrounds Massively Change the Apparent Size, Shape and Orientation of Flashed Test Squares. (November 2017) - Anstis, Stuart; Cavanagh, Patrick
A random-dot background was expanded and contracted, and rotated, or expanded in one dimension while contracting on the other, or skewed back and forth horizontally. Squares that were flashed at the reversal points of these affine pattern distortions, aligned to edges in the texture, showed massive changes in size and shape.